Risk Management in Road Transportation of Goods: Case Study of the Selected Company - Agnieszka BARCIK; Piotr DZIWINSKI (Communications of International Proceedings, 2021)
The risk in road transport is characterized by a measure of danger or a danger arising from events beyond of control or which are the consequences of specific decisions taken earlier. Risk management combines both functions - monitoring a certain field and minimizing the occurrence of any threats in it. Transport, however, is associated with a certain probability, which assumes that the load will not always reach the customer on time or intact or it will not reach him at all. Risk management has become one of the integral elements of the management strategy of every activity, including transport. It consists in predicting potential threats and trying to minimize their effects. Due to the high dependence of road transportation on random events and third-party activities, risk management is particularly important for this industry - both on the part of carriers and administrative units. The aim of this study is to identify the greatest threats to a transport company and to present the best solutions that can minimize and reduce these risks. The performed research will allow to answer the following research issues: identification of the risks in the transport company (determining their frequency and impact on the company); determining the risk level in the enterprise that transports goods; formulation of the risk mitigation measures used in transport.
Keywords: Risk Management; Road Transportation Management; Flow of Goods.